Correlation on Population Dynamics and Disease Incidence Of Bacterial Wilt Instigating Pathogen (Ralstonia Solanacearum) Under Different Intercropping System - Yonzone, R; Khalko, S; Sharma, BR; Hembram, S; Devi, M Soniya; Das, B (Bangladesh Journal of Botany, 2022)
Ginger (Zingiber officinale Rose) is one of the important spice crops grown organically in the hill zone of West Bengal. Among the various diseases that cause constrains to the organic ginger production Ralstonia solanacearum causes serious threats to the ginger growers. An experiment was conducted to study the influence of different intercropping patterns on yield, population dynamics, and disease incidence of R. solanacearumin ginger crop under organic management practice. Observation on population dynamics of R. solanacearum under different intercropping patterns revealed that the marigold when intercropped with ginger had a maximum influence on population build-up during 2019 and 2020. Also, it has the potentialities to reduce the population load thereby reducing the disease incidence and increasing the rhizome yield. Therefore, marigold can be incorporated as an intercrop in organic ginger cultivation for reducing the bacterial wilt disease. Bangladesh J. Bot. 51(4): 807-812, 2022 (December)